Evaluating the Effectiveness of Thai Basil Extract in Managing Type 2 Diabetes - Nathirat Charoensup; Loryuenyong Ruksiriwanich; Maneeton Juruwan (Journal of Advances in Medicine and Pharmaceutical Sciences, 2024)
This study investigated the potential of Ocimum basilicum var. thyrsiflora (Thai basil) extract as a natural adjunct therapy for the management of type 2 diabetes. The increasing prevalence of diabetes globally and the limitations of conventional therapies require alternative approaches, especially in regions where Thai basil is culturally accepted. The objective was to evaluate the effects of Thai basil on blood glucose levels and glycemic control in patients with type 2 diabetes. A randomized controlled trial was conducted in 2024 with 200 participants, aged 30–65 years, diagnosed with type 2 diabetes. Participants were assigned to either the Thai basil extract group (500 mg daily) or the placebo group, with clinical data collected at baseline, mid-intervention, and post-intervention. Findings showed that the intervention group experienced significant reductions in fasting blood glucose and HbA1c levels, indicating improved long-term glycemic control. In addition, lipid profiles, including cholesterol and triglyceride levels, were positively affected. However, no significant weight loss was observed. This review highlights the therapeutic potential of Thai basil bioactive compounds, including flavonoids and essential oils, which have antioxidant, anti-inflammatory, and antidiabetic properties. Limitations such as sample size and study duration are noted, indicating the need for further studies with larger, more diverse populations and longer duration. Future studies should explore the optimal dosage, formulation, and long-term effects of Thai basil. This study supports the inclusion of Thai basil in diabetes care, especially in regions where basil is widely available and culturally accepted.